Finding of remarkable synergistic effect on the aroxyl‐radical‐scavenging rates under the coexistence of α‐tocopherol and catechins. Issue 9 (9th May 2019) - Mukai, Kazuo; Nagai, Kanae; Ouchi, Aya; Suzuki, Tomomi; Izumisawa, Katsuhiro; Nagaoka, Shin‐Ichi
Abstract: Measurements of aroxyl radical (ArO )‐scavenging rate constants ( k s AOH ) of antioxidants (AOHs) (α‐tocopherol (α‐TocH) and three catechins (CatHs) (ie, epicatechin (EC), epigallocatechin (EGC), and epigallocatechin gallate (EGCG)) were performed in ethanol solution, using stopped‐flow spectrophotometry. k s AOH values were measured not only for each AOH, but also for the mixtures of two AOHs (α‐TocH and CatH). A notable synergistic effect that the k s α - TocH value of α‐TocH increases 1.29, 1.84, and 1.65 times under the coexistence of constant concentrations of EC, EGC, and EGCG, respectively, was observed for the solutions including α‐TocH and CatH. Similarly, k s CatH values of CatHs (EC, EGC, and EGCG) increased 1.72, 2.25, and 2.34 times under the coexistence of constant concentrations of α‐TocH, respectively. UV‐Vis absorption of α‐tocopheroxyl radical (α‐Toc ) (λmax  = 428 nm), which had been produced by reaction of α‐TocH with ArO, decreased remarkably under the coexistence of α‐TocH and CatHs due to the fast α‐TocH‐regeneration reaction by CatHs. The result suggests that the prooxidant reaction due to α‐Toc is suppressed by the coexistence of CatHs. By analyzing the formation and decay curves of α‐Toc, it has been ascertained that one molecule of EGCG having three OH groups at B‐ring may rapidly regenerate three molecules of α‐Toc to α‐TocH.